Adherence to Mediterranean diet impacts gastrointestinal microbial diversity throughout pregnancy - Corrie B. Miller; Paula Benny; Jonathan Riel; Carol Boushey; Rafael Perez; Vedbar Khadka; Yujia Qin; Alika K. Maunakea; Men-Jean Lee (BMC, 2021)
Abstract Background Consumption of a diet with high adherence to a Mediterranean diet pattern (MDP) has been associated with a favorable gastrointestinal tract (GIT) microbiome. A healthy GIT microbiome in pregnancy, as defined by increased alpha diversity, is associated with lower chance of adverse perinatal outcomes. This study aimed to evaluate the impact of adherence to an MDP on GIT microbial diversity longitudinally throughout pregnancy. Methods Adherence to MDP was scored by the Alternate Mediterranean (aMED) Diet Quality Score, after being applied to a validated Food Frequency Questionnaire. Association of aMED Scores with GIT alpha diversity profiles were compared linearly and across time using a linear mixed model, including covariates of age, body mass index (BMI), ethnicity, and parity. Results Forty-one participants of Filipino, Japanese, Native Hawaiian, and Non-Hispanic White descent provided dietary information and microbiome samples during each trimester of pregnancy. Alpha diversity profiles changed over gestation, with decreased microbial diversity in the third trimester. aMED scores positively correlated with Chao1 Index and Observed Species Number (r = 0.244, p = 0.017, and r = 0.233, p = 0.023, respectively). The strongest association was detected in the third trimester (Chao 1: r = 0.43, p = 0.020, Observed Species Number: r = 0.41, p = 0.026). Participants with higher aMED scores had higher relative abundance of Acidaminoacaeae at the family level (p = 0.0169), as well as higher abundance of several species known to increase production of short chain fatty acids within the GIT. Conclusions Adherence to MDP pattern is associated with increased maternal GIT microbial diversity, and promotes the abundance of bacteria that produce short chain fatty acids. Increased consumption of fruits, vegetables and legumes with low red meat consumption were key components driving this association. The effect of nutrition however, was less of an effect than pregnancy itself. Further studies are needed to determine if adherence to a Mediterranean diet translates not only into microbial health, but also into reduced risk of adverse pregnancy outcomes.